Об особой формуле среднего значения тока в электроцепи с управляемыми диодами и индуктивной нагрузкой - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2008)
A new formula for the mean value of current in the electric circuit with controlled diods and an inductive load is deduced with the use of a singular expansion of a jump-like function.